2020
DOI: 10.1007/s11165-020-09966-2
|View full text |Cite
|
Sign up to set email alerts
|

Science and Religious Education Teachers’ Views of Argumentation and Its Teaching

Abstract: Argumentation, the justification of claims with reasons and/or evidence, has emerged as a significant educational goal in science education in recent years. It has also been noted as an important pedagogical approach in numerous school subjects. Yet, there is limited understanding of how teachers’ views of argumentation and its teaching compare in different school subjects. In order to ensure coherence in the implementation of the school curriculum, it is important to understand such views particularly in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 57 publications
1
25
0
2
Order By: Relevance
“…Example 1: Jon considers that the concept of race in humans is not biologically meaningful because “sequencing the DNA of human genomes showed that two people picked from any place in the world share about 99% of their DNA sequences” (Beckwith et al, 2017 , p. 533). This argument is solid (valid) as it is accompanied by evidence (Erduran et al, 2020 ). Example 2: Tobi maintains that the concept of race in humans is biologically meaningful because “the 5 racial groups are Africans, Native Americans, Eurasians, East Asians, and Pacific Islanders.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Example 1: Jon considers that the concept of race in humans is not biologically meaningful because “sequencing the DNA of human genomes showed that two people picked from any place in the world share about 99% of their DNA sequences” (Beckwith et al, 2017 , p. 533). This argument is solid (valid) as it is accompanied by evidence (Erduran et al, 2020 ). Example 2: Tobi maintains that the concept of race in humans is biologically meaningful because “the 5 racial groups are Africans, Native Americans, Eurasians, East Asians, and Pacific Islanders.…”
Section: Resultsmentioning
confidence: 79%
“…After identifying Jon and Tobi’s arguments, undergraduate students were asked to evaluate arguments based on the question, “Are Jon and Tobi’s arguments solid?” (the third phase in Appendix 1 ). According to Erduran et al ( 2020 ), an argument is solid (sound, valid) when it is accompanied by reason and/or evidence. It is important to bear in mind that the arguments presented by Jon and Tobi are all solid (Beckwith et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations